ANALISIS PERHITUNGAN PAJAK PENGHASILAN BADAN CV. ALVINDO PRATAMA - Listya Devi Junaidi; Anjras Puspita (UNIVERSITAS DHARMAWANGSA, 2022)
PPh is a tax imposed on tax subjects on income received or earned in the form of taxes. It is one of the most essential items in a country as a source of income used to pay government spending. In Indonesia, taxes are a significant source of state revenue for long-term growth, as tax revenues rise in tandem with the country's economy and level of life in the context of self-sufficiency in financing national development. The goal of this research was to examine how CV. Alvindo Pratama calculated corporate income tax under Law No. 7 of 1983, as amended by Law No. 7 of 1991, Law No. 10 of 1994, Law No. 17 of 2000, Law No. 36 of 2008, Government Regulations, Presidential Decrees, Ministerial Decrees, Director General of Taxes Decrees, and Circulars of the Director General of Taxes. This is a qualitative study utilizing a descriptive method. The researcher attempts to present facts in conformity with current reality without interfering with the circumstances. Data collected from the company in the form of financial statements produced by CV. Alvindo Pratama is the source of data used in this work. The results reveal that CV. Alvindo Pratama's tax calculations are accurate and up to date, and that he pays and reports Corporate Income Tax on time.